answersLogoWhite

0

3b - 2 equals 7b plus 4?

User Avatar

Wiki User

โˆ™ 2010-07-03 15:34:56

Best Answer

3b -2 =7 b+4

User Avatar

Wiki User

โˆ™ 2010-07-03 15:34:56
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

Multiplication chart! :)

12 cards

2x1

2x2

2x3

2x4

โžก๏ธ
See all cards

Math and Arithmetic

20 cards

The length of a rectangular floor is 2 feet more than its width The area of the floor is 168 square feet Kim wants to use a rug in the middle of the room and leave a 2 foot border of the floor visib

The perimeter of a rectangle is 18 feet and the area of the rectangle is 20 square feet what is the width of the rectangle

The sum of two numbers is 19 and their product is 78 What is the larger number

A rectangular garden has a perimeter of 48 cm and an area of 140 sq cm What is the width of this garden

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: 3b - 2 equals 7b plus 4?
Write your answer...
Submit
Related questions

What is 26 equals 3b-2-7b?

3b - 7b - 2 = 26 then , -2 - 4b = 26 then , 4b = 26 then you do , -4 / 26 which equals 7


3b-2 equals 7b plus 4?

If b = -1.5 then -4.5 -2 = -10.5 + 4, which is true.


What is 26 equals 3b - 2 -7b?

26 = 3b - 2 - 7b 28 = -4b b = -7


No answer this problem and show work 3b-2 equals 7b plus 4?

Add 2 to each side: 3b = 7b + 6 Subtract 7b from each side: -4b = 6 Divide each side by 4: -b = 1.5 Change sign: b = -1.5


2-3b equals 7b plus 12?

2 - 3b = 7b + 12 Let us introduce equal terms (3b - 12 in this specific case) on each side (left and right) of the equal sign, so that the 'b' term is all alone on one side of the equal sign. 2 - 3b + (3 b - 12) = 7b + 12 + (3 b - 12) -10 = 10b b = -1 =============================


What is the simplest form of this expression.6(-3b-1) 2(7b-1)?

If you mean: 6(-3b-1)+2(7b-1) then it is -4b-8 simplified


What is the answer to 3b plus 6 equals 12?

3b + 6 = 12 3b = 6 b = 2


Does a plus b plus 2 plus 3 equals 2a plus 3b?

a+b+2+3=5+a+b


What is 20 plus 3b when b equals -6?

20+3b = 20 + 3(-6) = 20-18 = 2


How do you solve 3b plus 2a equals 2 and -2 plus a equals 8?

3b + 2a = 2 and -2 + a = 8 -2 + a = 8 can be rearranged to show a = 8 + 2 = 10 (Effectively 2 has been added to both sides.) As a = 10, the value for a can now be substituted in the equation 3b + 2a = 2 3b + 2x10 = 2 : 3b + 20 = 2 this can be rearranged to show 3b = 2 - 20 = -18 and dividing both sides by 3 gives b = -6.


-2b plus 7-3b equals 2?

-2b + 7 -3b = 2 -2b +7 -3b +2b = 2 + 2b 7 -3b + 3b = 2 + 2b +3b 7-2 = 2-2 + 2b + 3b 5 = 5b 1 = b


How do you factor b2 - 7b plus 12?

b^2 - 7b + 12 = b^2 - 4b - 3b + 12 = b(b -4) -3(b - 4) = (b - 3)(b - 4)


If 8b plus 11-3b equals 2b plus 2 what is b?

8b + 11 - 3b = 2b + 2 5b + 11 = 2b + 2 5b - 2b = 2 - 11 3b = -9 b = -3


How do you factor 49x2 plus 42xb plus 9b2?

(3b + 7x)(3b + 7x) or (3b + 7x)2


What is 2a plus 3b equals 6ab?

With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)


What is 12 minus 7b plus 10b equals 18?

First lets set up the equation.12 - 7b + 10b = 18.Now lets combine all like terms on the left hand side.12 - 7b + 10b = 1812 + 3b = 18Now lets combine all like terms using the like terms on the left side and on the right side.12 + 3b = 18-12 -123b = 6Now lets divided (since the 3 is being multiplied to the b).3b/3 = 6/3So your final answer is:b = 2


5a 2 plus 3b 2 plus 2a 2 plus 4b 2?

20a2b2


What is 10b-2 equals 7b-7.4?

N=3.1


What is the simplest form for 5b plus 5-3b-7?

5b plus 5-3b-7 is 2b-2.


9b plus 7 equals 19 plus 3b?

This simplifies to 6b = 12 so b = 2. Check: (9 x 2) + 7 = 25, 19 + (3 x 2) = 25 OK


What is a-7 equals 3b plus 2?

It is a linear equation in two unknown variables, a and b. It can be simplified (slightly) but cannot be solved becasue to solve with two unknowns you need two independent equations. Incidentally, a + 5 = (a - 7) + 12 = (3b + 2) +12 = 3b +14


Can someone factor this 3b to the 2 power -13b plus 10?

(b - 1)(3b - 10)


What is the answer to 2a plus 7b equals -1 3a - 7b equals -5?

2a + 7b = -13a - 7b = -5The system of equations can be solved by elimination:2a + 3a = -65a = -6a = -6/5substitute the value of a in any of the two original equations to find the value of b:2(-6/5) + 7b = -1-12/5 + 1 = -7b-7/5 = -7bb= 1/5


How do you factor ab plus 2a plus 3b plus 6?

(a + 3)( b + 2)


4a plus 2 equals 3b-5?

The equation cannot be solved as there are two unknowns. However it can be simplified and the two unknowns (a and b) expressed in terms of the second unknown. 1) Expressing a in terms of b 4a + 2 = 3b - 5 4a = 3b -7 if desired this could be stated as a = (3b - 7)/4 2) Expressing b in terms of a 3b - 5 = 4a + 2 3b = 4a + 7 if desired this could be stated as b = (4a + 7)/3